Lifestyles represented in the population of pharmacy students - Milošević Georgiev, Andrijana; Krajnović, Dušanka; Šesto, Sofija; Stamatović, Sara (Archives of Pharmacy, 2022)
Youth health is one of the most important indicators of a healthy potential of the nation, therefore its preservation and strengthening are of priority. Applying healthy lifestyle habits from an early age reduces the possibility of various disorders in further life. The objectives of the study were to examine the behaviors and opinions of students of the Faculty of Pharmacy, University of Belgrade, regarding healthy lifestyles. Data collection was conducted in November 2019 at the Faculty of Pharmacy in Belgrade, included 290 respondents; predominantly from the fourth year of study (41.7%). Tobacco use is present in 11.7%, and over half (61.7%) consume alcohol and coffee (75.2%). When it comes to nutrition, fruits are consumed daily by 22.4% of students, vegetables by 40.7% and meat by 41%. Eating in fast food restaurants is practiced by 68.5% of respondents. Only 3.5% of respondents report doing basic physical activity daily. 71.6% of students have regular sleep. 27.2% of students cannot afford a healthy lifestyle due to their financial status. The results indicate that healthy lifestyles are insufficiently represented in the student population, and interventions in changing student habits are desirable.